Application of Financial Statements of Micro, Small and Medium Enterprises (MSMEs) Based on Financial Accounting Standards of Micro, Small and Medium Entities (SAK-EMKM) - Rosa Nikmatul Fajri; Amalia Zulfat; Marsuking Marsuking; Kusumaningdiah Retno Setiorini (Edumedia Solution, 2022)
The purpose of this study is to provide input in the preparation of Optima Digital Printing financial statements to comply with Financial Accounting Standards for Micro, Small and Medium Enterprises (SAK-EMKM). The method used in this study is a qualitative method. The data used are primary data and secondary data, in primary data researchers make observations and interviews and SAK-EMKM. Secondary data is documentation obtained from the financial statement data of Optima Digital Printing. The result of this study is that Optima Digital Printing does not apply financial statement recording standards in accordance with SAK-EMKM in its financial statements.